Is the Polonia rate predictable on WIBOR O/N? - Miłobędzki, Paweł (Czy stawkę Polonia można prognozować, wykorzystując WIBOR O/N?, 2020)
The paper reports on whether the Polonia rate showing the price of one-day money in Poland is predictable on WIBOR O/N, its banking industry mid-morning forecast. In what follows the analysis is nested within the ARDL approach to a cointegration framework. Having the error correction model estimated on the daily sampled data from the period 24 Jan 2005 to31 Dec 2019, the paper simulated 100 sequences of the one-day dynamic Polonia rate forecasts up to 30 April 2020, the trading day preceding a significant modification of the WIBOR’s setting mechanism resulting in the late afternoon disclosure of the overnight rate estimates. The author also computed 95% confidence bands for those forecasts. The analysis shows that the error correction model specified on the Akaike information criterion performs well both in and out of the sample. Nevertheless, it slightly overestimated the actual Polonia rate at times when the monetary authority cuts the reference rate or shortly after that. In such circumstances the actual rate incidentally goes beyond the lower confidence band
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 47-55